The Shifting Structure of the Maltese Economy: Evidence from Chain-Linked Data - Darmanin, Jude; Montebello, Roberta; Deguara, Warren (Richtmann Publishing, 2021)
The economy of the Maltese islands has undergone significant structural change and diversification since the turn of the century. The aim of this study is to provide an overview of sectoral developments in output, employment, unit labour costs, and prices in Malta during the two decades to 2020. Analysis is conducted using the newly-available chain-linked sectoral national accounts data, which is a departure from previous studies. Furthermore, we complement our findings with a comparative analysis of structural developments in Malta and in the euro area. The results show that the Maltese economy underwent a significant shift towards the services sector between 2000 and 2020. Sectors such as finance & insurance, information & communication, professional, scientific & technical activities, administrative & support services, and arts, entertainment & recreational services saw large increases in their shares of both output and employment. On the other hand, more traditional sectors such as manufacturing, construction, and food & accommodation services saw a decline in their relative importance.Â An analysis of productivity and cost developments also suggests that services sectors were generally the most productive during the period under study, while recording the highest levels of compensation per employee and the lowest unit labour costs. Nonetheless, sectoral productivity levels in Malta generally remain below those observed in the euro area. Output prices rose significantly in Malta between 2000 and 2020, generally reflecting the higher pace of economic growth when compared with the euro area. Â Received: 29 May 2021 / Accepted: 2 July 2021 / Published: 8 July 2021